Perfectionism as predictors of anxiety and depression - Lauri Korajlija, Anita; Begić, Dražen; Jokić-Begić, Nataša (2008)
The dual process model of perfectionism suggests that there are both positive and negative aspects to perfectionism. Our aim was to determine the association between both positive and negativeperfectionism and anxiety and depression. The study included 40 clinically depressed, 41 clinically anxious and 43 control subjects, who completed the Beck depression Inventory, the State-Trait anxiety Inventory and the Positive and negative perfectionism scale. Negative perfectionism was found to be directly related to anxiety and indirectly to depression, with anxiety as a mediator variable. Negative perfectionism was shown to be a good predictor of anxiety and could be used as a good predictor of depression only in combination with trait anxiety. Positive perfectionism was not related toeither depression or anxiety, which makes it a desirable trait.
Projekt MZOS
ENG